Relationship between Live Streaming Features and Consumer Purchase Intention in the Context of Malaysian E-Commerce - Teow, Yi Fang; Zulkipli, Hafizah (Research in Management of Technology and Business, 2025)
Technological advancements have transformed consumer-business interactions, leading to the rapid expansion of e-commerce. A notable development within this domain is live streaming commerce, which integrates real-time interactive live streaming with online shopping. The COVID-19 pandemic significantly accelerated the growth of e-commerce in Malaysia, with live streaming emerging as a powerful tool to engage consumers and drive sales. The pandemic has precipitated long-lasting shifts in consumer behavior and habits, necessitating a deeper comprehension of the factors influencing purchase intentions. This study aims to explore the relationship between live streaming features and consumer purchase intention in the context of Malaysian e-commerce, focusing specifically on Malaysian consumers. A sample of 391 respondents was selected from approximately 33.4 million people in Malaysia. This study used a quantitative approach and questionnaires to gather primary data, which was then analyzed using SPSS software to achieve the study's objectives. The findings reviewed there is a significant relationship between live streaming features and consumer purchase intention in the context of Malaysian e-commerce. Despite this study being limited to technology and platform dependencies and temporal limitation, it provided valuable insights for future researchers and platform developers to learn more effectiveness of specific live streaming features.